The importance of organizational culture for business success - Ghaleb, Belal Dahiam Saif (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Organizational culture plays a crucial role in shaping the behavior, attitudes and effectiveness of employees in a business. This article explores the critical role of organizational culture in business success. A solid organizational culture aligns with strategic goals, increases employee performance and satisfaction, fosters innovation and maintains competitive advantage. Through a comprehensive review of the literature and case studies, this article identifies key elements such as leadership, communication, continuous improvement, and cultural diversity as important factors that influence organizational culture. The findings highlight that a positive and adaptive culture not only supports organizational resilience but also serves as a sustainable source of competitive differentiation. This study highlights that businesses need to consciously develop and evolve their culture in order to be successful in a dynamic market environment. The findings also show that a well-defined and positive organizational culture is effective in achieving long-term business success.